2015 IEEE International Black Sea Conference on Communications and Networking (BlackSeaCom) 2015
DOI: 10.1109/blackseacom.2015.7185094
|View full text |Cite
|
Sign up to set email alerts
|

SC-LDPC codes over the block-fading channel: Robustness to a synchronisation offset

Abstract: Spatially-Coupled LDPC (SC-LDPC) codes have been recently shown to be very efficient for transmissions over nonergodic channels, in particular over block-fading channels [1]. In fact, it is possible to design a SC-LDPC code with any given code diversity [2]. In this work, we investigate the performance of SC-LDPC codes over block-fading channels, assuming a mismatch (or offset) between the first bit of a transmission packet and a first bit of a codeword. Such a mismatch is called the synchronisation offset, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…First we allowed the burst erasure to take on any length and assumed that its starting position can occur anywhere in the codeword. Bursts of random starting positions have also been investigated in [22], although for different reasons and applications (synchronization). Additionally, we assumed that the parts of the codeword not affected by the burst are affected by a memoryless noise process.…”
Section: Introductionmentioning
confidence: 99%
“…First we allowed the burst erasure to take on any length and assumed that its starting position can occur anywhere in the codeword. Bursts of random starting positions have also been investigated in [22], although for different reasons and applications (synchronization). Additionally, we assumed that the parts of the codeword not affected by the burst are affected by a memoryless noise process.…”
Section: Introductionmentioning
confidence: 99%
“…in an increased required window length and thus also in an increased complexity. Recently, it has been shown that protograph-based LDPC codes can increase the diversity order of block fading channels and are thus good candidates for block erasure channels [7], [8]; however, they require large syndrome former memories if the burst length becomes large. Closely related structures based on protographs have been proposed in [9] which spatially couple the special class of root-check LDPC codes [10] to improve the finite length performance and thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…For latency constrained comparison using window decoding, see[3],[11].The increase of d IT for SC-LDPC codes come at increase of m cc and, thus, of the decoding latency.…”
mentioning
confidence: 99%